Implementasi Kesehatan Mental Zakiah Daradjat dalam Menghadapi Problematika Remaja di Lingkungan Pendidikan Pondok Pesantren - Muhammad Nurrosyid Huda Setiawan; A’maluna Karimata M. Nur (Proceedings Series on Social Sciences & Humanities, 2023)
The problems of adolescents in Indonesia are currently a very serious problem, as are the problems currently being faced by adolescents at Pondok Modern Darussalam Gontor Putri Campus 5. Problems with studying, friendships, cottage tasks, finances, health, and even in the realm of family, society and even religion, have become more of a concern for the lives of adolescents and will affect their development. According to the concept of mental health that has been presented by Zakiah Daradjat in dealing with problems that exist in a person's life, it usually occurs in early adolescence. This is because adolescence is a transitional period in the process of developing children towards adulthood which requires more attention in solving their life problems. In this case, Zakiah Daradjat's mental health concept provides a solution in solving problems that occur in adolescents. This is field research by making female students of class 3 intensive and 4 at Pondok Modern Darussalam Gontor Putri Campus 5 the main objects. The collection of research data is based on the results of interviews, questionnaires, and documentation. So the psychological approach is very instrumental in completing this research. After collecting data from the following research, it can be found that the mental health concept of Zakiah Daradjat has been successfully applied through the education system provided by Pondok Modern Darussalam Gontor Putri Campus 5 in the form of Tauiyyah Diniyyah and Qudwah Hasanah to shape the character of female students with noble character and obedience to religious teachings.